Idea of Synergistic and Comprehensive Treatment of Malignant Tumors with Traditional Chinese Medicine Discussed from Theory of “Cancer State” - Zhong LI (Zhongliu Fangzhi Yanjiu)
Cancer is a major public health problem worldwide, and although synergistic and comprehensive treatment with traditional Chinese medicine (TCM) has made some promising achievements in recent years, the prevention and treatment situation remains considerably serious. For optimizing the role of Chinese medicine in the clinic to fight against cancer, inheriting and innovating at the same time are necessary. The author, inspired by clinical and classical theories, innovatively put forward the theory of “cancer state” and proposed that the root of cancer treatment is to change the “cancer state”. In this study, I reflect on the current situation of TCM synergistic treatment of malignant tumors and analyze “cancer state theory”, with the hope of enriching the theoretical base of TCM evidence-based treatment of malignant tumors and providing new ideas and references for the individualized use of medicines in the clinical TCM evidence-based treatment of malignant tumors.